Risk from Prosperity: Eurodollar Market and Emerging Markets - Czeczeli, Vivien; Kutasi, Gábor (Public Finance Quarterly, 2025)
The Eurodollar market is out of US monetary targets, but favorite ﬁnancing item of emerging markets. Global economic prosperity raise the demand for Eurodollar loans but Fed’s dollar supply is not linked to the Eurodollar market. This generate an increasing risk in the emerging markets in proportion with their demand for Eurodollar ﬁnancing. This can have an unwanted backslash on both emerging markets risk premium. After an extensive explanation of the risk mechanism, the paper analyze the linkage between US interest rates as a proxy of business cycle and the CDS premia of emerging countries between 2008 and 2024 on daily bases with VECM estimates. The results conﬁrms that, in global prosperity indicated by lower US interest rate, the emerging countries with bigger exposure in external debt suﬀer bigger rise in their CDS premium as their risk indicator. Because of their higher cost of these countries can beneﬁt less from growth trajectory of global business cycle and increase their risk of default.